Perancangan Buku Pop-Up sebagai Panduan Menghadapi Menstruasi pada Anak Perempuan Sekolah Dasar - Maria Veronika Br Halawa; Regita Nur Amalia Putri; Sunarsih Sunarsih (YASIN, 2026)
Menstruation is a biological process experienced by females as part of the reproductive cycle. However, the lack of education and limited access to information about menstruation still give rise to negative stigma in society, particularly among girls who are just entering puberty. This condition may affect children’s physical, psychological, and social aspects, so an educational medium that is engaging, communicative, and child-friendly is needed. This design aims to produce an educational medium in the form of a pop-up book as a means to help girls understand and face menstruation more positively. The design was carried out using the Design Thinking method, which consists of five stages, namely empathize, define, ideate, prototype, and test. Data were collected qualitatively through interviews, surveys, and literature study, then analyzed using the SWOT approach to evaluate the strengths, weaknesses, opportunities, and threats of the developed design concept. The design results show that a pop-up book can serve as an engaging and child-friendly educational medium for conveying information about menstruation. This medium helps improve girls’ understanding of menstruation and builds awareness of the importance of reproductive health from an early age. The conclusion of this design affirms that a pop-up book has relevance as a visual-interactive educational medium to reduce menstruation stigma and support girls’ readiness in facing puberty. The implications of this design provide practical contributions for parents, educators, and related parties in providing menstruation education media that are informative, communicative, and suited to children’s characteristics.